1961
DOI: 10.1139/o61-132
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence and Distribution of Free Alkaloid Solanidine in Netted Gem Potatoes

Abstract: Free alkaloid solanidine was detected in concentrations up to 200 p.p.m. or 337, of the total glycoalkaloid level in bitter Netted Gem potatoes. Dormant tubers of this variety are readily induced to a rapid glycoalkaloid synthesis by exposure to intense solar radiation and near-freezing temperatures, conditions frequently encountered during the potato harvest in northern areas. Under such conditions solanidine is rapidly produced in excess of amounts that could be bound as solanine, the formation of which woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The slowest moving component corresponded to the pure solanine preparation, the second moved only slightly faster and is possibly chaconine, and the third may be the free alkaloid solanidine or another glycoalkaloid (Shih & Kuc 1974). The presence of three alkaloids in the tuber extracts supports the suggestion by Zitnak (1961) that further work on the toxicities of the glycoalkaloids and free alkaloids is required. He considers that solanidine is considerably more toxic than the glycoalkaloids and that its possible presence in tubers should be investigated.…”
Section: Resultssupporting
confidence: 79%
“…The slowest moving component corresponded to the pure solanine preparation, the second moved only slightly faster and is possibly chaconine, and the third may be the free alkaloid solanidine or another glycoalkaloid (Shih & Kuc 1974). The presence of three alkaloids in the tuber extracts supports the suggestion by Zitnak (1961) that further work on the toxicities of the glycoalkaloids and free alkaloids is required. He considers that solanidine is considerably more toxic than the glycoalkaloids and that its possible presence in tubers should be investigated.…”
Section: Resultssupporting
confidence: 79%
“…This could be linked to curing delaying reducing sugar accumulation which occurs when tubers are chilled at harvest (Burton 1989). Support for this suggestion follows the detection of high concentrations of solanidine in tubers of cv Netted Gem after exposure to intense solar radiation and near zero temperatures (Zitnak, 1961). Under these conditions Zitnak (1 961) suggested solanidine is produced rapidly in excessive quantities that could be bound as solanine, the formation of which could be limited by the availability of glycosidic sugar components.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally it was suggested that the presence of salt, sugars or glycoalkaloids do not enhance potato flavour although their presence at high levels may decrease palatability. For example, several studies suggested high levels of glycoalkaloids are responsible for off-flavours in potato tubers (Zitnak, 1961;Sinden et al, 1976;Ross et al, 1978).…”
Section: Introductionmentioning
confidence: 99%